Charge Transfer Between d-p States in Ti02 By Employing Compton Scattering Techniques - Mobammad, F.M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The com pton profiles for Ti02 have been measured using a SCiAm-241 compton spectrometer .A pellet of the oxide was prepared from a polycrystalline powder    having a thickness of 1.54 mm ,about J 00000  counts   have   been  accumulated   at   the  compton   peak.Theoreti cal compton profiles have been calculated for different ionic anangements using free atom compton profile for the core electrons.The   theoretical  and  experimental  results  ahrce  well  for (Ti/4(0 .2    arrangement which support complete transfer of valence electrons from metal to oxygen ions, i.e., full ionic  bonding in this oxide in agreement with available pbotoemission and other studies .